2022
DOI: 10.1093/eurheartj/ehac544.2618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interleukin-6 inhibition with ziltivekimab in patients at high risk of atherosclerotic events in Japan: results from the phase 2 RESCUE-2 trial

Abstract: Introduction In the US phase 2 RESCUE trial, ziltivekimab, a fully human monoclonal antibody against the ligand of the pro-inflammatory cytokine interleukin-6, was shown to reduce biomarkers of inflammation in patients with chronic kidney disease (CKD) and elevated levels of high-sensitivity C-reactive protein (hsCRP), a marker of inflammation and cardiac risk.1 Here, we present outcomes from the phase 2 RESCUE-2 trial of ziltivekimab in a patient population from Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the RESCUE study, a significant decrease of hsCRP concentration in all doses of ziltivekimab tested was demonstrated (−87.8% reduction in the 30 mg cohort) [35]. Smaller studies have confirmed this effect in different populations [37 ▪ ]. The ongoing Effects of Ziltivekimab Versus Placebo on Cardiovascular Outcomes in Participants With Established Atherosclerotic Cardiovascular Disease, Chronic Kidney Disease and Systemic Inflammation (ZEUS – NCT05021835) trial will test whether targeting of the interleukin-6 ligand will translate to an improved cardiovascular outcome [38].…”
Section: Pharmacological Treatments Inflammatory Burden and C-reactiv...mentioning
confidence: 88%
“…In the RESCUE study, a significant decrease of hsCRP concentration in all doses of ziltivekimab tested was demonstrated (−87.8% reduction in the 30 mg cohort) [35]. Smaller studies have confirmed this effect in different populations [37 ▪ ]. The ongoing Effects of Ziltivekimab Versus Placebo on Cardiovascular Outcomes in Participants With Established Atherosclerotic Cardiovascular Disease, Chronic Kidney Disease and Systemic Inflammation (ZEUS – NCT05021835) trial will test whether targeting of the interleukin-6 ligand will translate to an improved cardiovascular outcome [38].…”
Section: Pharmacological Treatments Inflammatory Burden and C-reactiv...mentioning
confidence: 88%
“…26 A novel IL-6 antagonist ziltivekimab has demonstrated potential efficacy for cardiovascular risk reduction in a phase II trial. 27 While IL-1 and IL-6 antagonists are not of clinical use in SpA, whether their use might reduce cardiovascular risk in SpA might be an avenue for future exploration. Surprisingly, lower levels of TNF-α were associated with SCA in our study.…”
Section: Discussionmentioning
confidence: 99%